Determination of 60 pesticides in hen eggs using the QuEChERS procedure followed by LC-MS/MS and GC-MS/MS. (15th November 2019) - Song, Nho-Eul; Lee, Jun Young; Mansur, Ahmad Rois; Jang, Hae Won; Lim, Min-Cheol; Lee, Yunyeol; Yoo, Miyoung; Nam, Tae Gyu
Highlights: A technique was developed for determining 60 multi-residue pesticides in eggs. The quick, easy, cheap, effective, rugged, safe sample-preparation method was used. Gas and liquid chromatographies were used to determine pesticide levels. Validation data reveal good linearities, recoveries, specificities, and precisions. The method can be used to routinely monitor pesticide residues in egg samples. Abstract: An analytical method involving QuEChERS (quick, easy, cheap, effective, rugged, and safe) sample preparation, followed by LC-MS/MS and GC-MS/MS was developed and validated for the determination of 60 pesticides in eggs. Recoveries of 70–120% were achieved for selected pesticides and relative standard deviations <20% were obtained for most analytes at three concentrations. The limit of quantification was <10 µg kg −1 for 83% of the total pesticides. This method was used to analyze 58 egg samples and the residues of seven pesticides (disulfoton, fipronil sulfone, cyromazine, o, p-DDT, p, p-DDD, p, p-DDT, and permethrin) were quantified in 16 egg samples at levels of 5–10 µg kg −1, which was below the corresponding the maximum residue levels, as established by Korean Ministry of Food and Drug Safety. We demonstrated that LC-MS/MS and GC-MS/MS in combination with QuEChERS can be used to routinely monitor multiple pesticide residues in egg samples.